(untitled) - Stewart, John Robert (Boston, MA., 2002)
Bridges not Walls examines interpersonal communication through a broad range of scholarly and popular articles drawn from various disciplines, including communication, philosophy, social science, and psychology. Readings included are thought-provoking discussions of the nature of interpersonal contact, connections between verbal and nonverbal cues, person perception and social intelligence, listening, deception and betrayal, identity management, interpersonal ethics, types of love, transformational conflict management, and diversity.
Keywords: Interpersonal communication